Green Air Inc. / Hanis Shaziera Khaidzir - Khaidzir, Hanis Shaziera (2020)
Green Air Inc. is a company that produce Mini Portable Air Conditioner. Our company will be the main provider for this product at an affordable price and good quality. Our product aim to solve the customer problem in our country, Malaysia that having difficulties due to the hot weather. People who are constantly working under the sun or even those who are in the building can use this product. Another main reasons for the invention of this product is to reduce the global warming by using the latest technology. It is known that the components in the standard air conditioner usually contains high toxicity substances such as chlorofluorocarbons (CFCs) which is known to be dangerous and harmful for the Earth’s ozone. Our product will omit the use of all these dangerous substances. The production of Mini Portable Air Conditioner is such a great ideas towards our environment and hopefully will give a fierce competition among the air conditioner industry. Since our company, Green Air Inc. is the first to invent this air conditioner with the latest technology, we hope to be the main supplier and customer’s first choice for this product.